2022
DOI: 10.3892/ol.2022.13325
|View full text |Cite
|
Sign up to set email alerts
|

Metformin: A promising drug for human cancers (Review)

Abstract: Small-molecule chemical drugs are of great significance for tumor-targeted and individualized therapies. However, the development of new small-molecule drugs, from basic experimental research and clinical trials to final application in clinical practice, is a long process that has a high cost. It takes at least 5 years for most drugs to be developed in the laboratory to prove their effectiveness and safety. Compared with the development of new drugs, repurposing traditional non-tumor drugs can be a shortcut. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 104 publications
0
18
0
Order By: Relevance
“…Moreover, having a drug with a unique chemical feature, multiple therapeutic targets, high safety therapeutic margin, and affordable economic cost [64,65] may contribute to reducing mortality and improving recovery due to pandemic diseases; for example, COVID-19 and its fatal complications.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, having a drug with a unique chemical feature, multiple therapeutic targets, high safety therapeutic margin, and affordable economic cost [64,65] may contribute to reducing mortality and improving recovery due to pandemic diseases; for example, COVID-19 and its fatal complications.…”
Section: Discussionmentioning
confidence: 99%
“…By blocking angiotensin II receptor signalling, losartan prevents angiotensin II from increasing the levels of thrombospondin-1, a major activator of TGF-β, and thus suppresses TGF-β signalling and other profibrotic signals. Preclinical trials with models of breast cancer and PDAC showed that losartan reduced the amount of collagen and hyaluronan intratumorally and significantly improved perfusion by decompressing tumour vessels [ 127 , 128 ]. Seven clinical trials are currently recruiting in PDAC, breast cancer, osteosarcoma, and myelogenous leukaemia ( , accessed on 1 February 2023).…”
Section: Therapeutical Targetsmentioning
confidence: 99%
“…Metformin is a 1,1-dimethylbiguanide hydrochloride that is extracted from the legume Galega officinalis [ 13 ]. Metformin is widely used to treat type 2 diabetes [ 14 ].…”
Section: Introductionmentioning
confidence: 99%